Board-level codetermination: A driving force for corporate social responsibility in German companies?. (September 2019) - Scholz, Robert; Vitols, Sigurt
We examine the relationship between board-level codetermination and corporate social responsibility in German companies, engaging with two distinct literatures. Most quantitative studies of codetermination focus on its economic impact, with little attention to other outcomes. Studies of corporate social responsibility rarely consider the role of worker representatives. Our new measure of the strength of codetermination, the Mitbestimmungsindex (MB-ix), shows a positive relationship with 'substantive' policies such as the adoption of targets for reducing pollution, but not with 'symbolic' policies, such as membership of the UN Global Compact. We therefore shed new light on the role of codetermination and provide a more differentiated view of the spread of what has been termed 'explicit' corporate social responsibility in Germany.